Nigeria's Growth Record : Dutch Disease Or Debt Overhang ? - Wijnbergen, Sweder van, 1951- 1951- (The World Bank, 2007)
Nigeria's oil boom has not brought an end to perennial stagnation in the non-oil economy. Is this the unavoidable consequence of the resource boom or have misguided policies contributed? This paper indicates that the extreme volatility of expenditure rather than Dutch Disease effects are behind the disappointing non-oil growth record. Fiscal policies failed to smooth highly volatile oil income; on the contrary government expenditure was more volatile than oil income. The authors provide econometric evidence showing that volatility of expenditure was increased by debt overhang problems. Moreover, they also find evidence of voracity effects that exacerbated expenditure volatility prior to 1984